2022
DOI: 10.1021/acs.jcim.2c00526
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Properties Representation Scheme for Recurrent Neural Network-Based Prediction of Therapeutic Peptides

Abstract: The discovery of therapeutic peptides is often accelerated by means of virtual screening supported by machine learning-based predictive models. The predictive performance of such models is sensitive to the choice of data and its representation scheme. While the peptide physicochemical and compositional representations fail to distinguish sequence permutations, the amino acid arrangement within the sequence lacks the important information contained in physicochemical, conformational, topological, and geometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…To further demonstrate the power of the ETFC model, we compare it with the existing methods. To improve the reproducibility and reliability of MPMABP ( Li et al 2022 ), MLBP ( Tang et al 2022 ), sequential properties-recurrent neural network (SP-RNN) ( Otović et al 2022 ) and PrMFTP ( Yan et al 2022 ), we provide the hyperparameter details of these models in Supplementary Tables S4–S7 , respectively. The comparison of ETFC with MPMABP, MLBP, SP-RNN, and PrMFTP is performed on the test set, and we randomly selected 80% of the set as the subset and repeated this process five times to obtain five subsets.…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the power of the ETFC model, we compare it with the existing methods. To improve the reproducibility and reliability of MPMABP ( Li et al 2022 ), MLBP ( Tang et al 2022 ), sequential properties-recurrent neural network (SP-RNN) ( Otović et al 2022 ) and PrMFTP ( Yan et al 2022 ), we provide the hyperparameter details of these models in Supplementary Tables S4–S7 , respectively. The comparison of ETFC with MPMABP, MLBP, SP-RNN, and PrMFTP is performed on the test set, and we randomly selected 80% of the set as the subset and repeated this process five times to obtain five subsets.…”
Section: Resultsmentioning
confidence: 99%
“…A suitable algorithm guiding conjugate design based on activity, serum stability and penetration capability would be desirable to speed up the development process. While algorithms derived from random peptide library design [ 91 ], machine learning-based predictive models [ 92 ] and natural sequence scanning [ 93 ] have been proposed for predicting peptide bioactivity, unfortunately, no such tool is yet available for peptide–antiviral-drug conjugate activity. Future studies should also focus on PDCs with various therapeutic profiles for further development in stability and performance.…”
Section: Pdc Design Considerationsmentioning
confidence: 99%
“…Furthermore, Capecchi et al [ 134 ] trained RNNs and identified eight non-hemolytic molecules that target different bacteria. Otovic et al [ 135 ] recently used a long-term generative memory RNN to engineer a PEP-137 peptide whose administration enhanced the survival rate to 50% in a murine model of Klebsiella pneumoniae -induced sepsis.…”
Section: Future Perspectives and Challenges Related To The Use Of Ant...mentioning
confidence: 99%